2006
DOI: 10.1161/01.str.0000195180.69904.f2
|View full text |Cite
|
Sign up to set email alerts
|

Susceptibility to Deterioration of Mobility Long-Term After Stroke

Abstract: Background and Purpose-The aim of the present study was to identify clinical determinants able to predict which individuals are susceptible to deterioration of mobility from 1 to 3 years after stroke. Methods-Prospective cohort study of stroke patients consecutively admitted for inpatient rehabilitation. A total of 205 relatively young, first-ever stroke patients were assessed at 1 and 3 years after stroke. Mobility status was determined by the Rivermead Mobility Index (RMI), and decline was defined as a deter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
124
3
3

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 202 publications
(133 citation statements)
references
References 45 publications
3
124
3
3
Order By: Relevance
“…Oko polovice svih preživjelih vrati se nekom zaposlenju, a 25 do 30 % nije sposobno funkcionirati bez pomoći druge osobe, 2 što najviše zabrinjava bolesnike te dovodi do nastajanja psiholoških problema i problema socijalne integracije. 3 Zahvaljujući promijenjenom načinu života i smanjenju faktora rizika, boljem zbrinjavanju bolesnika, kako u primarnoj i sekundarnoj prevenciji tako i u akutnoj fazi, incidencija se moždanog udara u razvijenim zemljama smanjila, a mortalitet reducirao. Nažalost, manje razvijene zemlje, kao i zemlje u tranziciji, kojima pripada i Hrvatska, nisu podložne takvim promjenama.…”
Section: Uvodunclassified
“…Oko polovice svih preživjelih vrati se nekom zaposlenju, a 25 do 30 % nije sposobno funkcionirati bez pomoći druge osobe, 2 što najviše zabrinjava bolesnike te dovodi do nastajanja psiholoških problema i problema socijalne integracije. 3 Zahvaljujući promijenjenom načinu života i smanjenju faktora rizika, boljem zbrinjavanju bolesnika, kako u primarnoj i sekundarnoj prevenciji tako i u akutnoj fazi, incidencija se moždanog udara u razvijenim zemljama smanjila, a mortalitet reducirao. Nažalost, manje razvijene zemlje, kao i zemlje u tranziciji, kojima pripada i Hrvatska, nisu podložne takvim promjenama.…”
Section: Uvodunclassified
“…As many stroke patients survives with evident declined mobility [20], various interventions have been proposed that target improving mobility of stroke survivors. A systematic review of stroke rehabilitation in 2007 revealed [14] Randomized controlled trails (RCT) that involved gait-oriented training defined as training intended to improve gait performance in terms of various gait parameters such as stride/step frequency, stride/step length, endurance and walking speed [5].…”
Section: Motor Recovery Following Motor Rehabilitationmentioning
confidence: 99%
“…Additionally, some characteristics of the living area of the participants such as mountains, uneven grounds or stones could be barriers for those who could walk independently. Independent walking is often used as an indicator of functional recovery in stroke 24 , and limitations in walking would cause other musculo-skeletal complications as well as further dependence in the activities of daily living and social isolation 6 . For instance being unable to walk would be a barrier to return to work, or to participate in different social events.…”
Section: Activity Limitations Experiencedmentioning
confidence: 99%
“…Understanding the challenges faced by those who have suffered a stroke is useful to identify the longer-term issues that primary care based services for stroke will need to address 3 . Studies which investigated the functional challenges experienced by stroke patients revealed that the main activity limitations experienced are inability to walk independently, dependence on bathing, eating and dressing, as well as in housework activities such as washing, cooking and cleaning 4,5,6 . A study conducted in South Africa to determine the limitations in activity and participation experienced by community-dwelling stroke survivors discharged from an intensive inpatient rehabilitation programme at 6 months post stroke revealed that many participants were not independent in housework, food preparation, shopping, and public transport use 7 .…”
Section: Introductionmentioning
confidence: 99%